2019
DOI: 10.1038/s41556-019-0343-0
|View full text |Cite
|
Sign up to set email alerts
|

Myc and Dnmt1 impede the pluripotent to totipotent state transition in embryonic stem cells

Abstract: Totipotency refers to the ability of a cell to generate all of the cell types of an organism. Unlike pluripotency, the establishment of totipotency is poorly understood. In mouse embryonic stem cells, Dux drives a small percentage of cells into a totipotent state by expressing 2-cell-embryospecific transcripts. To understand how this transition takes place, we performed single-cell RNAseq, which revealed a two-step transcriptional reprogramming process characterized by downregulation of pluripotent genes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
138
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(153 citation statements)
references
References 56 publications
12
138
2
1
Order By: Relevance
“…6c, d ). Unlike previous studies which overexpressed a master regulator, Dux, to induce 2C-like state 27 , we did not observe a significant decrease in Sox2 expression in the intermediate state ( Supplementary Fig. 6c ), highlighting the potential difference between the Dux-induced 2C-transitions and the naturally occurring pluripotent-to-totipotent transition process.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…6c, d ). Unlike previous studies which overexpressed a master regulator, Dux, to induce 2C-like state 27 , we did not observe a significant decrease in Sox2 expression in the intermediate state ( Supplementary Fig. 6c ), highlighting the potential difference between the Dux-induced 2C-transitions and the naturally occurring pluripotent-to-totipotent transition process.…”
Section: Resultscontrasting
confidence: 99%
“…DNA-binding proteins, such as TFs and epigenetic regulators, show rapid gene expression changes during pluripotent-to-2C transition 27, 29 . Our analysis of immediate transcription changes during the pluripotent-to-2C transition identified 26 genes encoding DNA-binding proteins that showed a significant difference at new RNA levels between states ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the large-scale epigenetic and transcriptional changes that occur during the maternal-to-zygotic transition (reviewed in Eckersley-Maslin, Alda-Catalinas & Reik 2018), we hypothesized that maternal epigenetic and transcriptional factors have crucial roles in regulating ZGA and consequently focused our screen on such candidate regulators. Due to the technical limitations of high-throughput screening in early embryos, we used mouse ESC as an in vitro proxy to mimic ZGA (Eckersley-Maslin, Alda-Catalinas & Reik 2018;Fu et al 2019;Yan et al 2019;Eckersley-Maslin et al 2019;Rodriguez-Terrones et al 2018), reasoning that overexpression of ZGA regulators may induce a ZGA-like transcriptional signature which can be captured by scRNA-seq.…”
Section: A Crispr-activation Screen For Zga Regulators At Single-cellmentioning
confidence: 99%
“…Recent studies have shown that a ZGA-like state can be mimicked in mouse ESCs (Macfarlan et al 2012;Zalzman et al 2010;Bošković et al 2014;Ishiuchi et al 2015;Akiyama et al 2015;Eckersley-Maslin et al 2016;Rodriguez-Terrones et al 2018). Consequently, these cells represent an ideal system for in vitro screening and have been previously used to identify regulators of ZGA (Fu et al 2019;Yan et al 2019;Eckersley-Maslin et al 2019;Rodriguez-Terrones et al 2018). While most of these studies probing ZGA regulators in ESCs have focused on repressors (Fu et al 2019;Rodriguez-Terrones et al 2018), positive inducers of ZGA have thus far not been interrogated in a systematic manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation